Experimental determination of the electrostatic nature of carbonyl hydrogen-bonding interactions using IR-NMR correlations - Kashid, Somnath M.; Bagchi, Sayan (Journal of Physical Chemical Letters, 2014)
Hydrogen-bonding plays a fundamental role in the structure, function, and dynamics of various chemical and biological systems. Understanding the physical nature of interactions and the role of electrostatics in hydrogen-bonding has been the focus of several theoretical and computational research. We present an experimental approach involving IR-C-13 NMR correlations to determine the electrostatic nature of carbonyl hydrogen-bonding interactions. This report provides a direct experimental evidence of the classical nature of hydrogen-bonding interaction in carbonyls, independent of any theoretical approximation. These results have important implications in chemistry and biology and can be applied to probe the reaction mechanisms involving carbonyl activation/stabilization by hydrogen bonds using spectroscopic techniques.

Non-uniform early structural response of globular proteins to cold denaturing conditions: a case study with Yfh1 - Chatterjee, Prathit; Bagchi, Sayan; Sengupta, Neelanjana (Journal of Chemical Physics, 2014)
The mechanism of cold denaturation in proteins is often incompletely understood due to limitations in accessing the denatured states at extremely low temperatures. Using atomistic molecular dynamics simulations, we have compared early (nanosecond timescale) structural and solvation properties of yeast frataxin (Yfh1) at its temperature of maximum stability, 292 K (T-s), and the experimentally observed temperature of complete unfolding, 268 K (T-c). Within the simulated timescales, discernible ``global'' level structural loss at T-c is correlated with a distinct increase in surface hydration. However, the hydration and the unfolding events do not occur uniformly over the entire protein surface, but are sensitive to local structural propensity and hydrophobicity. Calculated infrared absorption spectra in the amide-I region of the whole protein show a distinct red shift at T-c in comparison to T-s. Domain specific calculations of IR spectra indicate that the red shift primarily arises from the beta strands. This is commensurate with a marked increase in solvent accessible surface area per residue for the beta-sheets at T-c. Detailed analyses of structure and dynamics of hydration water around the hydrophobic residues of the beta-sheets show a more bulk water like behavior at T-c due to preferential disruption of the hydrophobic effects around these domains. Our results indicate that in this protein, the surface exposed beta-sheet domains are more susceptible to cold denaturing conditions, in qualitative agreement with solution NMR experimental results. (C) 2014 AIP Publishing LLC.

Cosolvent effects on solute-solvent hydrogen-bond dynamics: ultrafast 2D IR investigations - Kashid, Somnath M.; Jin, Geun Young; Bagchi, Sayan; Kim, Yung Sam (Journal of Physical Chemistry B, 2015)
Cosolvents strongly influence the solute-solvent interactions of biomolecules in aqueous environments and have profound effects on the stability and activity of several proteins and enzymes. Experimental studies have previously reported on the hydrogen-bond dynamics of water molecules in the presence of a cosolvent, but understanding the effects from a solute's perspective could provide greater insight into protein stability. Because carbonyl groups are abundant in biomolecules, the current study used 2D IR spectroscopy and molecular dynamics simulations to compare the hydrogen-bond dynamics of the solute's carbonyl group in aqueous solution, with and without the presence of DMSO as a cosolvent. 2D IR spectroscopy was used to quantitatively estimate the time scales of the hydrogen-bond dynamics of the carbonyl group in neat water and 1:1 DMSO/water solution. The 2D IR results show spectral signatures of a chemical exchange process: The presence of the cosolvent was found to lower the hydrogen-bond exchange rate by a factor of 5. The measured exchange rates were 7.50 X 10(11) and 1.48 X 10(11) s(-1) in neat water and 1:1 DMSO/water, respectively. Molecular dynamics simulations predict a significantly shorter carbonyl hydrogen-bond lifetime in neat water than in 1:1 DMSO/water and provide molecular insights into the exchange mechanism. The binding of the cosolvent to the solute was found to be accompanied by the release of hydrogen-bonded water molecules to the bulk. The widely different hydrogen-bond lifetimes and exchange rates with and without DMSO indicate a significant change in the ultrafast hydrogen-bond dynamics in the presence of a cosolvent, which, in turn, might play an important role in the stability and activity of biomolecules.

Correlating Nitrile IR frequencies to local electrostatics quantifies noncovalent interactions of peptides and proteins - Deb, Pranab; Haldar, Tapas; Kashid, Somnath M.; Banerjee, Subhrashis; Chakrabarty, Suman; Bagchi, Sayan (Journal of Physical Chemistry B, 2016)
Noncovalent interactions, in particular the hydrogen bonds and nonspecific long-range electrostatic interactions are fundamental to biomolecular functions. A molecular understanding of the local electrostatic environment, consistently for both specific (hydrogen-bonding) and nonspecific electrostatic (local polarity) interactions, is essential for a detailed understanding of these processes. Vibrational Stark Effect (VSE) has proven to be an extremely useful method to measure the local electric field using infrared spectroscopy of carbonyl and nitrile based probes. The nitrile chemical group would be an ideal choice because of its absorption in an infrared spectral window transparent to biomolecules, ease of site-specific incorporation into proteins, and common occurrence as a substituent in various drug molecules. However, the inability of VSE to describe the dependence of IR frequency on electric field for hydrogen-bonded nitriles to date has severely limited nitrile's utility to probe the noncovalent interactions. In this work, using infrared spectroscopy and atomistic molecular dynamics simulations, we have reported for the first time a linear correlation between nitrile frequencies and electric fields in a wide range of hydrogen-bonding environments that may bridge the existing gap between VSE and H-bonding interactions. We have demonstrated the robustness of this field-frequency correlation for both aromatic nitriles and sulfur-based nitriles in a wide range of molecules of varying size and compactness, including small molecules in complex solvation environments, an amino acid, disordered peptides, and structured proteins. This correlation, when coupled to VSE, can be used to quantify noncovalent interactions, specific or nonspecific, in a consistent manner.

Electrostatic interactions are key to C=O n-pi* shifts: an experimental proof - Haldar, Tapas; Bagchi, Sayan (Journal of Physical Chemistry Letters, 2016)
Carbonyl n-pi* transitions are known to undergo blue shift in polar and hydrogen-bonding solvents. Using semiempirical expressions, previous studies hypothesized several factors like change in dipole moment and hydrogen-bond strength upon excitation to cause the blue shift. Theoretically, ground-state electrostatics has been predicted to be the key to the observed shifts, however, an experimental proof has been lacking. Our experimental results demonstrate a consistent linear correlation between IR (ground-state phenomenon) and n-pi* frequency shifts (involves both ground and excited electronic-states) of carbonyls in hydrogen-bonded and non-hydrogen-bonded environments. The carbonyl hydrogen-bonding status is experimentally verified from deviation in n-pi*/fluorescence correlation. The IR/n-pi* correlation validates the key role of electrostatic stabilization of the ground state toward n-pi* shifts and demonstrates the electrostatic nature of carbonyl hydrogen bonds. n-pi* shifts show linear sensitivity to calculated electrostatic fields on carbonyls. Our results portray the potential for n-pi* absorption to estimate local polarity in biomolecules and to probe chemical reactions involving carbonyl activation/stabilization.

Pick and choose the spectroscopic method to calibrate the local electric field inside proteins - Haldar, Tapas; Kashid, Somnath M.; Deb, Pranab; Kesh, Sandeep; Bagchi, Sayan (Journal of Physical Chemistry Letters, 2016)
Electrostatic interactions in proteins play a crucial role in determining the structure function relation in biomolecules. In recent years, fluorescent probes have been extensively employed to interrogate the polarity in biological cavities through dielectric constants or semiempirical polarity scales. A choice of multiple spectroscopic methods, not limited by fluorophores, along with a molecular level description of electrostatics involving solute-solvent interactions, would allow more flexibility to pick and choose the experimental technique to determine the local electrostatics within protein interiors. In this work we report that ultraviolet/visible-absorption, infrared-absorption, or C-13 NMR can be used to calibrate the local electric field in both hydrogen bonded and non-hydrogen bonded protein environments. The local electric field at the binding site of a serum protein has been determined using the absorption wavelength as well as the carbonyl stretching frequency of its natural steroid substrate, testosterone. Excellent agreement is observed in the results obtained from two independent spectroscopic techniques.

Two-dimensional infrared spectroscopy reveals cosolvent-composition-dependent crossover in intermolecular hydrogen bond dynamics - Kashid, Somnath M.; Jin, Geun Young; Chakrabarty, Suman; Kim, Yung Sam; Bagchi, Sayan (Journal of Physical Chemistry Letters, 2017)
Cosolvents have versatile composition-dependent applications in chemistry and biology. The simultaneous presence of hydrophobic and hydrophilic groups in dimethyl sulfoxide (DMSO), an industrially important amphiphilic cosolvent, when combined with the unique properties of water, plays key roles in the diverse fields of pharmacology, cryoprotection, and cell biology. Moreover, molecules dissolved in aqueous DMSO exhibit an anomalous concentration-dependent nonmonotonic behavior in stability and activity near a critical DMSO mole fraction of 0.15. An experimental identification of the origin of this anomaly can lead to newer chemical and biological applications. We report a direct spectroscopic observation of the anomalous behavior using ultrafast twodimensional infrared spectroscopy experiments. Our results demonstrate the cosolventconcentration-dependent nonmonotonicity arises from nonidentical mechanisms in ultrafast hydrogen-bond-exchange dynamics of water above and below the critical cosolvent concentration. Comparison of experimental and theoretical results provides a molecular-level mechanistic understanding: a distinct difference in the stabilization of the solute through dynamic solute solvent interactions is the key to the anomalous behavior.

Interconverting hydrogen-bonding and weak n -> pi* interactions in aqueous solution: A direct spectroscopic evidence - Deb, Pranab; Jin, Geun Young; Singh, Santosh K.; Moon, Juran; Kwon, Hyejin; Das, Aloke; Bagchi, Sayan; Kim, Yung Sam (Journal of Physical Chemistry Letters, 2018)
Molecular structure and function depend on myriad noncovalent interactions. However, the weak and transient nature of noncovalent interactions in solution makes them challenging to study. Information on weak interactions is typically derived from theory and indirect structural data. Solvent fluctuations, not revealed by structure analysis, further complicate the study of these interactions. Using 2D infrared spectroscopy, we show that the strong hydrogen bond and the weak n -> pi* interaction coexist and interconvert in aqueous solution. We found that the kinetics of these interconverting interactions becomes faster with increasing water content. This experimental observation provides a new perspective on the existence of weak noncovalent interactions in aqueous solution.

Arresting an unusual amide tautomer using divalent cations - Kashid, Somnath M.; Singh, Reman K.; Kwon, Hyejin; Kim, Yung Sam; Mukherjee, Arnab; Bagchi, Sayan (Journal of Physical Chemistry B, 2019)
Ion-specific effects on peptides and proteins are key to biomolecular structure and stability. The subtle roles of the cations are far less understood, compared to the pronounced effects of the anions on proteins. Most importantly, divalent cations such as Ca2+ and Mg2+ are crucial to several biological functions. Herein, we demonstrate that an amide-iminolate equilibrium is triggered by the binding of the divalent cations to the amide oxygen in aqueous solution. The excellent agreement between the experimental and theoretical results confirms the arrest of an unusual amide tautomer by the divalent cations, which is a rarely known phenomenon that might open up an array of applications in chemistry and biology.

Hydrocarbon chain-length dependence of solvation dynamics in alcohol-based deep eutectic solvents: a two-dimensional infrared spectroscopic investigation - Chatterjee, Srijan; Ghosh, Deborin; Haldar, Tapas; Deb, Pranab; Sakpal, Sushil S.; Deshmukh, Samadhan H.; Kashid, Somnath M.; Bagchi, Sayan (Journal of Physical Chemistry B, 2019)
Deep eutectic solvents (DESs) have gained popularity in recent years as an environmentally benign, inexpensive alternative to organic solvents for diverse applications in chemistry and biology. Among them, alcohol-based DESs serve as useful media in various applications due to their significantly low viscosity as compared to other DESs. Despite their importance as media, little is known how their solvation dynamics change as a function of the hydrocarbon chain length of the alcohol constituent. In order to obtain insights into the chain-length dependence of the solvation dynamics, we have performed two-dimensional infrared spectroscopy on three alcohol-based DESs by systematically varying the hydrocarbon chain length. The results reveal that the solvent dynamics slows down monotonically with an increase in the chain length. This increase in the dynamic timescales also shows a strong correlation with the concomitant increase in the viscosity of DESs. In addition, we have performed molecular dynamics simulations to compare with the experimental results, thereby testing the capacity of simulations to determine the amplitudes and timescales of the structural fluctuations on fast timescales under thermal equilibrium conditions.

Electrostatic manifestation of micro-heterogeneous solvation structures in deep-eutectic solvents: a spectroscopic approach - Chatterjee, Srijan; Haldar, Tapas; Ghosh, Deborin; Bagchi, Sayan (Journal of Physical Chemistry B, 2020)
Deep eutectic solvents have emerged as inexpensive green alternatives to conventional solvents for diverse applications in chemistry and biology. Despite their importance as useful media in various applications, little is known about the microscopic solvation structures of deep eutectic solvents around solutes. Herein, we show that the electrostatic field, which can be estimated both from infrared experiments and theory, can act as a unified concept to report on the microscopic heterogeneous solvation of deep eutectic solvents. Using a fluorophore containing the carbonyl moiety as the solute and the electrostatic field as a descriptor of the solvation structure of the deep eutectic solvents, we report the residue-specific distribution, orientation, and hydrogen bonding in deep eutectic solvents constituting of choline chloride and alcohols of varying chain-lengths. We observe that an increase in alcohol chain-length not only affects the alcohol's propensity to form hydrogen bond to the solute but also alters the spatial arrangement of choline cations around the solute, thereby leading to a microheterogeneity in the solvation structure. Moreover, to extend our electrostatic field based strategy to other deep eutectic solvents, we report an emission spectroscopy based method. We show that this method can be applied, in general, to all deep eutectic solvents, irrespective of their constituents. Overall, this work integrates experiments with molecular dynamics simulations to provide insights into the heterogeneous DES solvation.

Reply to “comment on ‘arresting an unusual amide tautomer using divalent cations’” - Kashid, Somnath M.; Singh, Reman K.; Kwon, Hyejin; Seol, Jin Gyu; Kim, Yung Sam; Mukherjee, Arnab; Bagchi, Sayan (Journal of Physical Chemistry B, 2020)
In our publication, we assigned the blue-shifted shoulder of N-methylacetamide (NMA) in the infrared (IR) spectrum (∼1645 cm<span style="outline: none; font-size: 12.75px; line-height: 0; position: relative; top: -0.5em; font-family: Roboto, arial, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 300;">–1) to an iminolate tautomer stabilized in the presence of divalent metal cations (e.g., 5 M Ca<span style="outline: none; font-size: 12.75px; line-height: 0; position: relative; top: -0.5em; font-family: Roboto, arial, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 300;">2+).<a class="ref ref1" style="outline: none; background-color: transparent; text-decoration-line: underline; color: rgb(26, 13, 171); transition: color 0.3s ease 0s; overflow-wrap: break-word; word-break: break-word; display: inline-block; font-family: Roboto, arial, sans-serif; font-size: 17px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 300;">(1) Cremer and co-workers comment that this shoulder arises from the dehydration of the amide oxygen upon interaction with the metal cations.<a class="ref ref1a ref2" style="outline: none; background-color: transparent; text-decoration-line: underline; color: rgb(26, 13, 171); transition: color 0.3s ease 0s; overflow-wrap: break-word; word-break: break-word; display: inline-block; font-family: Roboto, arial, sans-serif; font-size: 17px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 300;">(2,3) Their assignment is based on three interesting experimental observations: (1) the IR spectrum of <span style="outline: none; font-size: 12.75px; line-height: 0; position: relative; top: -0.5em; font-family: Roboto, arial, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 300;">15N-isotope-labeled NMA does not show any considerable red-shift compared to that of NMA; (2) a new peak appears for NMA at 1680 cm<span style="outline: none; font-size: 12.75px; line-height: 0; position: relative; top: -0.5em; font-family: Roboto, arial, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 300;">–1 in the presence of 1 M DCl, which shows a 17 cm<span style="outline: none; font-size: 12.75px; line-height: 0; position: relative; top: -0.5em; font-family: Roboto, arial, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 300;">–1 red-shift for <span style="outline: none; font-size: 12.75px; line-height: 0; position: relative; top: -0.5em; font-family: Roboto, arial, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 300;">15N-labeled NMA; and (3) the IR spectrum of acetone C═O stretch also demonstrates a blue-shifted shoulder in the presence of a high concentration of CaCl<span style="outline: none; font-size: 12.75px; line-height: 0; position: relative; bottom: -0.25em; font-family: Roboto, arial, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 300;">2.

Variations in activity of Ru/TiO(2 )and Ru/Al2O3 catalysts for CO2 hydrogenation: an investigation by in-situ infrared spectroscopy studies - Dongapure, Pavan; Bagchi, Sayan; Mayadevi, S.; Devi, R. Nandini (Molecular Catalysis, 2020)
CO2 hydrogenation to methane, an important reaction strategically and also for value adding to CO2, is investigated on two different catalysts, Ru supported on alumina as well as titania to understand better low temperature activity of Ru/TiO2 catalyst. In-situ infrared studies are carried out in three different steps, viz., (i) CO2 adsorption on fully reduced catalyst (ii) reaction of these adsorbed species with gaseous H-2 and (iii) under co-feed of CO2 and H-2, at different temperatures. On Ru/Al2O3 catalyst, CO2 reacts with hydroxyls on the support surface to form carbonate and adsorbs reductively on metal as CO. Further reduction to formate and methyl species occurs on reaction with H. Small concentration of the reactive intermediate formyl forms only at high temperatures. Whereas, bare TiO2 itself seems capable of reductive adsorption of CO2 as formate indicating enhanced reducibility of titania based catalyst. Formyl groups are observed at low temperatures in Ru/TiO2 in step (ii), which further forms methyl and gaseous methane at much lower temperatures when compared to alumina catalyst. Highly reactive CO species loosely bound to metal-support interface observed at high temperatures, which is not present on Ru/Al2O3 catalyst also makes this catalyst superior. In comparison, linearly bound CO seen in alumina catalyst is not as reactive.
Keywords: CO2 hydrogenation; In-situ infra red spectroscopy; Ru/Al2O3; Ru/TiO2

Curious case of aqueous warfarin: structural isomers or distinct excited states? - Sakpal, Sushil S.; Ghosh, Deborin; Manae, Meghna A.; Hazra, Anirban; Bagchi, Sayan (Journal of Physical Chemistry B, 2021)
Warfarin is a potent anti-coagulant drug and is on the World Health Organization's List of Essential Medicines. Additionally, it displays fluorescence enhancement upon binding to human serum albumin, making warfarin a prototype fluorescent probe in biology. Despite its biological significance, the current structural assignment of warfarin in aqueous solution is based on indirect evidence in organic solvents. Warfarin is known to exist in different isomeric forms-open-chain, hemiketal, and anionic forms-based on the solvent and pH. Moreover, warfarin displays a dual absorption feature in several solvents, which has been employed to study the ring-chain isomerism between its open-chain and hemiketal isomers. In this study, our pH-dependent experiments on warfarin and structurally constrained warfarin derivatives in aqueous solution demonstrate that the structural assignment of warfarin solely on the basis of its absorption spectrum is erroneous. Using a combination of steady-state and time-resolved spectroscopic experiments, along with quantum chemical calculations, we assign the observed dual absorption to two distinct pi ->pi* transitions in the 4-hydroxycoumarin moiety of warfarin. Furthermore, we unambiguously identify the isomeric form of warfarin that binds to human serum albumin in aqueous buffer.

Evidence of an nN(amide) → π*Ar interaction in N-Alkyl-N,N′-diacylhydrazines - Deka, Jugal Kishore Rai; Sahariah, Biswajit; Sakpal, Sushil S.; Bar, Arun Kumar; Bagchi, Sayan; Sarma, Bani Kanta (Organic letters, 2021)
1,2-Dibenzoyl-1-tert-butylhydrazine (RH-5849) and related N-alkyl-N,N′-diacylhydrazines are environmentally benign insect growth regulators. Herein, we show that an unusual n<span style="outline: none; font-size: 12.75px; line-height: 0; position: relative; bottom: -0.25em; font-family: Georgia, serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; background-color: rgb(244, 244, 244);">N(amide) → π*<span style="outline: none; font-size: 12.75px; line-height: 0; position: relative; bottom: -0.25em; font-family: Georgia, serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; background-color: rgb(244, 244, 244);">Ar interaction mediated by a hydrazide amide nitrogen atom plays a crucial role in stabilizing their biologically active trans–cis (t–c) rotameric conformations. We provide NMR and IR spectroscopic evidence for the presence of these interactions, which is also supported by X-ray crystallographic and computational studies.

Stabilization of Azapeptides by N-amide center dot center dot center dot H-N-amide Hydrogen Bonds - Baruah, Kalpita; Sahariah, Biswajit; Sakpal, Sushil S.; Deka, Jugal Kishore Rai; Bar, Arun Kumar; Bagchi, Sayan; Sarma, Bani Kanta (Organic Letters, 2021)
An unusual N-amide center dot center dot center dot H-Namide hydrogen bond (HB) was previously proposed to stabilize the azapeptide beta-turns. Herein we provide experimental evidence for the N-amide center dot center dot center dot H-Namide HB and show that this HB endows a stabilization of 1-3 kcal.mol(-1) and enforces the trans-cis-trans (t-c-t) and cis-cis-trans (c-c-t) amide bond conformations in azapeptides and N-methyl-azapeptides, respectively. Our results indicate that these N-amide center dot center dot center dot H-Namide HBs can have stabilizing contributions even in short azapeptides that cannot fold to form beta-turns.

Transition of a deep eutectic solution to aqueous solution: a dynamical perspective of the dissolved solute - Sakpal, Sushil S.; Deshmukh, Samadhan H.; Chatterjee, Srijan; Ghosh, Deborin; Bagchi, Sayan (Journal of Physical Chemistry Letters, 2021)
Disruption of the deep eutectic solvent (DES) nanostructure around the dissolved solute upon addition of water is investigated by polarization-selective two-dimensional infrared spectroscopy and molecular dynamics simulations. The heterogeneous DES nanostructure around the solute is partially retained up to 41 wt % of added water, although water molecules are gradually incorporated in the solute's solvation shell even at lower hydration levels. Beyond 41 wt %, the solute is observed to be preferentially solvated by water. This composition denotes the upper hydration limit of the deep eutectic solvent above which the solute senses an aqueous solvation environment. Interestingly, our results indicate that the transition from a deep eutectic solvation environment to an aqueous one around the dissolved solute can happen at a hydration level lower than that reported for the ``water in DES'' to ``DES in water'' transition.

Association-dissociation dynamics of ionic electrolytes in low dielectric medium - Ghosh, Deborin; Sakpal, Sushil S.; Chatterjee, Srijan; Deshmukh, Samadhan H.; Kwon, Hyejin; Kim, Yung Sam; Bagchi, Sayan (Journal of Physical Chemistry B, 2022)
Ionic electrolytes are known to form various complexes which exist in dynamic equilibrium in a low dielectric medium. However, structural characterization of these complexes has always posed a great challenge to the scientific community. An additional challenge is the estimation of the dynamic association-dissociation time scales (lifetime of the complexes), which are key to the fundamental understanding of ion transport. In this work, we have used a combination of infrared absorption spectroscopy, two-dimensional infrared spectroscopy, molecular dynamics simulations, and density functional theory calculations to characterize the various ion complexes formed by the thiocyanate-based ionic electrolytes as a function of different cations in a low dielectric medium. Our results demonstrate that thiocyanate is an excellent vibrational reporter of the heterogeneous ion complexes undergoing association-dissociation dynamics. We find that the ionic electrolytes exist as contact ion pairs, dimers, and clusters in a low dielectric medium. The relative ratios of the various ion complexes are sensitive to the cations. In addition to the interactions between the thiocyanate anion and the countercation, the solute-solvent interactions drive the dynamic equilibrium. We have estimated the association-dissociation dynamics time scales from two-dimensional infrared spectroscopy. The exchange time scale involving the cluster is faster than that between a dimer and an ion pair. Moreover, we find that the dynamic equilibrium between the cluster and another ion complex is correlated to the solvent fluctuations.

Blue fluorescence of cyano-tryptophan predicts local electrostatics and hydrogen bonding in biomolecules - Haldar, Tapas; Chatterjee, Srijan; Alam, Md Nirshad; Maity, Pradip; Bagchi, Sayan (Journal of Physical Chemistry B, 2022)
Cyano-tryptophan is an unnatural fluorescent amino acid that emits in the visible region. Along with the structural similarity with tryptophan, the unique photophysical properties of this fluorophore make it an ideal probe for biophysical research. Herein, combining fluorescence spectroscopy, infrared spectroscopy, and molecular dynamics simulations, we show that the cyano-tryptophan's emission energy quantifies the underlying bond-specific noncovalent interactions in terms of the electric field. We further report the use of fluorophore's emission energy to predict its hydrogen bond characteristics. We demonstrate that combining experiments with molecular dynamics simulations can provide the hydrogen bonding status of the nitrile moiety. In addition, we report a method to differentiate between aqueous and nonaqueous hydrogen-bonding partners. Using a phenomenological approach, we demonstrate that the presence of the cyano-indole moiety is responsible for the distinct correlations between the fluorophore's emission and the electrostatic forces on the nitrile bond. As indole is a privileged scaffold for both native amino acids and nucleobases, cyano-indoles will have many multifaceted applications.

Does viscosity drive the dynamics in an alcohol-based deep eutectic solvent? - Chatterjee, Srijan; Deshmukh, Samadhan H.; Bagchi, Sayan (Journal of Physical Chemistry B, 2022)
Deep eutectic solvents, consisting of heterogeneous nano-domains of hydrogen-bonded networks, have evolved into a range of viscous fluids that find applications in several fields. As viscosity is known to influence the dynamics of other neoteric solvents like ionic liquids, understanding the effect of viscosity on deep eutectic solvents is crucial to realize their full potential. Herein, we combine polarization-selective pump-probe spectroscopy, two-dimensional infrared spectroscopy, and molecular dynamics simulations to elucidate the impact of viscosity on the dynamics of an alcohol-based deep eutectic solvent, ethaline. We compare the solvent fluctuation and solute reorientation time scales in ethaline with those in ethylene glycol, an ethaline constituent. Interestingly, we find that the solute's reorientation apparently scales the bulk viscosity of the solvent, but the same is not valid for the overall solvation dynamics. Using the variations in the estimated intercomponent hydrogen bond lifetimes, we show that a dissolved solute does not sense the bulk viscosity of the deep eutectic solvent; instead, it senses domain-specific local viscosity determined by the making and breaking of the hydrogen bond network. Our results indicate that understanding the domain-specific local environment experienced by the dissolved solute is of utmost importance in deep eutectic solvents.

Ligand dynamics time scales identify the surface-ligandinteractions in thiocyanate-capped cadmium sulfide nanocrystals - Deshmukh, Samadhan H.; Chatterjee, Srijan; Ghosh, Deborin; Bagchi, Sayan (Journal of Physical Chemistry Letters, 2022)
The nanocrystal surface, which acts as an interface between thesemiconductor lattice and the capping ligands, plays a significant role in theattractive photophysical properties of semiconductor nanocrystals for use in awide range of applications. Replacing the long-chain organic ligands with shortinorganic variants improves the conductivity and carrier mobility of nanocrystal-based devices. However, our current understanding of the interactions betweenthe inorganic ligands and the nanocrystals is obscure due to the lack ofexperiments to directly probe the inorganic ligands. Herein, using two-dimensional infrared spectroscopy, we show that the variations in the inorganicligand dynamics within the heterogeneous nanocrystal ensemble can identifythe diversities in the inorganic ligand-nanocrystal interactions. The liganddynamics time scale in SCN-capped CdS nanocrystals identifies three distinctligand populations and provides molecular insight into the nanocrystal surface.Our results demonstrate that the SCN-ligands engage in a dynamic equilibriumand stabilize the nanocrystals by neutralizing the surface charges through both direct binding and electrostatic interaction.

On-off infrared absorption of the S=O vibrational probe of dimethyl sulfoxide - Chakrabarty, Suranjana; Deshmukh, Samadhan H.; Barman, Anjan; Bagchi, Sayan; Ghosh, Anup (Journal of Physical Chemistry B, 2022)
Dimethyl sulfoxide (DMSO), a polar solvent molecule, is used in a wide range of therapeutic and such as dimerization and hydrogen bonding with water, are crucial to understanding the role of DMSO in applications. Herein, we study DMSO in various solvation environments to decipher the environment-dependent dimerization and hydrogen-bonding propensity. We use a combination of infrared spectroscopy, quantum mechanical calculations, and molecular dynamics simulations to reach our conclusions. Although DMSO can exist in a dynamic equilibrium between monomers and dimers, our results show that the relative intensity of the S=O stretch and the CH3 rocking modes is a spectroscopic indicator of the extent of DMSO dimerization in solution. The dimerization (self-association) is seen to be maximum in neat DMSO. When dissolved in different solvents, the dimerization propensity decreases with increasing solvent polarity. In the presence of a protic solvent, such as water, DMSO forms a hydrogen bond with the solvent molecules, thereby reducing the extent of dimerization. Further, we estimate the hydrogen-bond occupancy of DMSO. Our results show that DMSO predominantly exists as doubly hydrogen-bonded in water.

Predicting the redox potentials of phenazine derivatives using DFT-assisted machine learning - Ghule, Siddharth; Dash, Soumya Ranjan; Bagchi, Sayan; Joshi, Kavita; Vanka, Kumar (ACS Omega, 2022)
This study investigates four machine-learning (ML) models to predict the redox potentials of phenazine derivatives in dimethoxyethane using density functional theory (DFT). A small data set of 151 phenazine derivatives having only one type of functional group per molecule (20 unique groups) was used for the training. Prediction accuracy was improved by a combined strategy of feature selection and hyperparameter optimization, using the external validation set. Models were evaluated on the external test set containing new functional groups and diverse molecular structures. High prediction accuracies of R2 > 0.74 were obtained on the external test set. Despite being trained on the molecules with a single type of functional group, models were able to predict the redox potentials of derivatives containing multiple and different types of functional groups with good accuracies (R2 > 0.7). This type of performance for predicting redox potential from such a small and simple data set of phenazine derivatives has never been reported before. Redox flow batteries (RFBs) are emerging as promising candidates for energy storage systems. However, new green and efficient materials are required for their widespread usage. We believe that the hybrid DFT-ML approach demonstrated in this report would help in accelerating the virtual screening of phenazine derivatives, thus saving computational and experimental costs. Using this approach, we have identified promising phenazine derivatives for green energy storage systems such as RFBs.

Water-controlled keto-enol tautomerization of a prebiotic nucleobase - Datar, Avdhoot; Paithankar, Harshad; Deb, Pranab; Chugh, Jeetender; Bagchi, Sayan; Mukherjee, Arnab; Hazra, Anirban (Journal of Physical Chemistry B, 2022)
Barbituric acid is believed to be a proto-RNA nucleobase that was used for biological information transfer on prebiotic earth before DNA and RNA in their present forms evolved. Nucleobases have various tautomeric forms and the relative stability of these forms is critical to their biological function. It has been shown that barbituric acid has a tri-keto form in the gas phase and an enol form in the solid state. However, its dominant tautomeric form in aqueous medium that is most relevant for biology has been investigated only to a limited extent and the findings are inconclusive. We have used multiple approaches, namely, molecular dynamics, quantum chemistry, NMR, and IR spectroscopy to determine the most stable tautomer of barbituric acid in solution. We find a delicate balance in the stability of the two tautomers, tri-keto and enol, which is tipped toward the enol as the extent of solvation by water increases.

Does variation in composition affect dynamics when approaching the eutectic composition? - Chatterjee, Srijan; Chowdhury, Tubai; Bagchi, Sayan (Journal of Chemical Physics, 2023)
Deep eutectic solvent is a mixture of two or more components, mixed in a certain molar ratio, such that the mixture melts at a temperature lower than individual substances. In this work, we have used a combination of ultrafast vibrational spectroscopy and molecular dynamics simulations to investigate the microscopic structure and dynamics of a deep eutectic solvent (1:2 choline chloride: ethylene glycol) at and around the eutectic composition. In particular, we have compared the spectral diffusion and orientational relaxation dynamics of these systems with varying compositions. Our results show that although the time-averaged solvent structures around a dissolved solute are comparable across compositions, both the solvent fluctuations and solute reorientation dynamics show distinct differences. We show that these subtle changes in solute and solvent dynamics with changing compositions arise from the variations in the fluctuations of the different intercomponent hydrogen bonds.

Solvation structure and dynamics of a small ion in an organic electrolyte - Kore, Shivshankar; Sahoo, Rudhi Ranjan; Santra, Binit; Sarkar, Archishman; Chowdhury, Tubai; Deshmukh, Samadhan H.; Hazarika, Sulagna; Chatterjee, Srijan; Bagchi, Sayan (Journal of Photochemistry and Photobiology A-Chemistry, 2023)
Organic carbonates are commonly used as electrolytes in commercial lithium-ion batteries. A detailed interpretation of the solvation structure and dynamics of the electrolyte around ions is necessary to understand the charge/discharge process in batteries. This work combines infrared absorption spectroscopy with quantum chemical calculations and molecular dynamics simulations to decipher the solvation structure of propylene carbonate, a cyclic carbonate, around the dissolved thiocyanate ion. Two dimensional infrared spectroscopy and polarization-selective pump probe spectroscopies have been utilized to extract the timescales of solvent fluctuation and the solute reorientational dynamics. The similarity in the slow timescales for the solute and the solvent dynamics signifies that similar processes control both dynamics.

Perturbation of fermi resonance on hydrogen-bonded > C=O: 2D IR studies of small ester probes - Sakpal, Sushil; Chakrabarty, Suranjana; Reddy, Kambham Devendra; Deshmukh, Samadhan H.; Biswas, Rajib; Bagchi, Sayan; Ghosh, Anup (Journal of Physical Chemistry B, 2024)
We utilized linear and 2D infrared spectroscopy to analyze the carbonyl stretching modes of small esters in different solvents. Particularly noteworthy were the distinct carbonyl spectral line shapes in aqueous solutions, prompting our investigation of the underlying factors responsible for these differences. Through our experimental and theoretical calculations, we identified the presence of the hydrogen-bond-induced Fermi resonance as the primary contributor to the varied line shapes of small esters in aqueous solutions. Furthermore, our findings revealed that the skeletal deformation mode plays a crucial role in the Fermi resonance for all small esters. Specifically, the first overtone band of the skeletal deformation mode intensifies when hydrogen bonds form with the carbonyl group of esters, whereas such coupling is rare in aprotic organic solvents. These spectral insights carry significant implications for the utilization of esters as infrared probes in both biological and chemical systems.

Probing surface interactions in CdSe quantum dots with thiocyanate ligands - Deshmukh, Samadhan H.; Yadav, Sushma; Chowdhury, Tubai; Pathania, Akhil; Sapra, Sameer; Bagchi, Sayan (NANOSCALE, 2024)
Keywords: COLLOIDAL NANOCRYSTALS; STRUCTURAL DYNAMICS; Thin-films

Slowdown of solvent structural dynamics in aqueous DMF solutions - Pathania, Akhil; Bagchi, Sayan (Chemical Physics Impact, 2024)
<span style="color: rgb(31, 31, 31); font-family: ElsevierGulliver, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif, sans-serif; font-size: 16px;">This study presents a comprehensive investigation into the molecular dynamics of solvation environments through an integrated approach combining Fourier-transform infrared (FTIR) spectroscopy, molecular dynamics (MD) simulations, and two-dimensional infrared (2D IR) spectroscopy. We explore the solvation of an ionic solute (ammonium thiocyanate) in various solvent systems, including N,N-dimethylformamide (DMF), water, and a 0.5 mole fraction of DMF in water, aiming to unravel the intricate interplay between solute-solvent interactions and solvent dynamics across diverse solvation environments. By integrating FTIR spectral analysis with radial distribution functions and coordination numbers obtained from MD simulations, we decipher the solvent composition around the solute molecule. Analysis of 2D IR spectra and hydrogen bond, as well as dipolar autocorrelation function from MD simulations, further elucidates the nuances of solute-solvent interactions, highlighting the impact of solvent dynamics on solvation structures. Our results reveal a significant slowdown of the solvent structural dynamics in the equimolar binary solvent mixture compared to the neat solvents. This slowdown underscores the complex relationship between solute-solvent interactions and solvent dynamics. The integration of FTIR, MD simulations, and 2D IR spectroscopy provides a unified framework for obtaining a holistic understanding of solvation dynamics, offering valuable insights into the underlying molecular mechanisms governing solute-solvent interactions in complex systems. These results pave the way for future studies to delve deeper into the molecular intricacies of solvation phenomena.

Solvation dynamics and microheterogeneity in deep eutectic solvents - Chatterjee, Srijan; Chowdhury, Tubai; Bagchi, Sayan (Journal of Physical Chemistry B, 2024)
Deep eutectic solvents have attracted considerable attention due to their unique properties and their potential to replace conventional solvents in diverse applications, such as catalysis, energy storage, and green chemistry. However, despite their broad use, the microscopic mechanisms governing solvation dynamics and the role of hydrogen bonding in deep eutectic solvents remain insufficiently understood. In this article, we present our contributions toward unravelling the micro heterogeneity within deep eutectic solvents by combining vibrational Stark spectroscopy and two-dimensional infrared spectroscopy with molecular dynamics simulations. Our findings demonstrate how the composition, constituents, and addition of water significantly influence the heterogeneous hydrogen bonding network and solvent dynamics within these systems. These insights provide valuable guidance for the design of next-generation solvents tailored to specific applications. By integrating experimental and computational approaches, this work sheds light on the intricate relationship between solvation dynamics and nanostructure in deep eutectic solvents, ultimately paving the way for innovative advances in solvent design.

Viscosity effects on the dynamics of diols and diol-based deep eutectic solvents - Chatterjee, Srijan; Deshmukh, Samadhan H.; Chowdhury, Tubai; Bagchi, Sayan (Photochemistry and Photobiology, 2024)
Diols, characterized by the presence of two hydroxyl groups, form extended hydrogen-bonded networks. Increasing hydrocarbon chain length is known to elevate the viscosity of diols. Given the established influence of viscosity on solvent dynamics, it becomes imperative to comprehend the impact of viscosity on the fluctuation dynamics within diols and establish connections with hydrogen bond formation and breaking dynamics. In this study, we employ two-dimensional infrared spectroscopy to investigate the viscosity dependence of the structural evolution dynamics in three diols with varying chain lengths. Complementing our experimental approach, molecular dynamics simulations are conducted to extract hydrogen bond lifetimes. Our findings reveal a linear correlation between bulk viscosity, solvent fluctuation timescales, and hydrogen bond lifetimes. Notably, the selected diols exhibit the capability to form deep eutectic solvents upon mixing with choline chloride at specific molar ratios. In contrast to molecular solvents like diols, deep eutectic solvents are characterized by the formation of heterogeneous nanodomains, comprising various intercomponent hydrogen-bonded networks. Interestingly, our observations indicate that while the fluctuation dynamics decelerate with increasing bulk viscosity in diol-based deep eutectic solvents, the relationship between viscosity and dynamics is not linear, in contrast to the observed linearity in diols. This nuanced understanding contributes to the broader comprehension of the interplay between viscosity and dynamics in both molecular and deep eutectic solvents. We investigate the impact of viscosity on structural evolution dynamics in diols with varying chain lengths. Employing two-dimensional infrared spectroscopy and molecular dynamics simulations, we explore the relationship between bulk viscosity, solvent fluctuation timescales, and hydrogen bond lifetimes. We report a linear correlation in diols between viscosity, fluctuation timescales, and hydrogen bond lifetimes. Diols also form deep eutectic solvents, characterized by heterogeneous nanodomains. While fluctuation dynamics slow down with increasing bulk viscosity in diol-based deep eutectic solvents, the relationship between viscosity and dynamics is nonlinear, contrasting with diols' linearity. This understanding enhances comprehension of viscosity-dynamics interplay in molecular and deep eutectic solvents.image
Keywords: Dynamics; Hydrogen bond; solvent; spectroscopy; viscosity

Probing solvent fluctuations in deep eutectic solvents: Influence of probe charge and nano-domain localization - Chowdhury, Tubai; Pathania, Akhil; Ravindranathan, Sapna; Bagchi, Sayan (Journal of Chemical Physics, 2025)
Deep eutectic solvents (DESs) segregate into hydrogen bond acceptor or hydrogen bond donor (HBD) rich nano-domains, leading to molecular heterogeneity. Understanding how this heterogeneity affects the DES structure and dynamics is essential. In this study, we used two-dimensional nuclear magnetic resonance (2D NMR) and two dimensional infrared (2D IR) spectroscopies, combined with molecular dynamics (MD) simulations, to investigate solvation structure and dynamics in two choline chloride-based DESs with different HBDs-levulinic acid and glycolic acid. We introduced two thiocyanate vibrational probes, methyl thiocyanate (CH3SCN, neutral) and ammonium thiocyanate (NH4SCN, anionic), which selectively localize in specific nano-domains. 2D NMR provided insights into solvent structure and probe location, while 2D IR captured solvation dynamics. Our results show that these small probes do not alter the solvent structure, regardless of charge. However, solvation dynamics depend on long-range electrostatic ordering in the DES and the local shielding effects of the nano-domain where the probe resides. MD simulations complement experimental findings, providing a molecular-level understanding of solvation in DESs.